Is there a Relationship between the Characteristics and Attitudes of Adolescents with Premarital Sex? - SiwiRizki Utami; Muthmainnah; Oedojo Soedirham; YuliPuspita Devi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Premarital sex is one of the high-risk behaviors of adolescents today. The characteristics of adolescents can also be a triggering factor for premarital sex. The purpose of this study was to analyze the relationship between characteristics and attitudes of adolescents towards premarital sex in East Java Province.Methods: This is a quantitative research with a cross sectional research design. The data used were taken from Program Performance and Accountability Survey (2018) on adolescents aged 15-24 years in East Java Province. The sample of this study was 2796 adolescents after normal weight adolescents were carried out. The dependent variable in this study is the attitude of adolescents, while the independent variables are place of residence, age, gender, education, and economic status. Data collection using smartphones and instruments that refer to the IDHS and PMA. The data were analyzed descriptively and tested using chi-square with a significance level of 0.05.Result and Conclusion: The results showed that the characteristics associated with the attitude of female adolescent was the place of residence with a significance value of 0.026. Age was related to the attitude of male adolescent with a significance value of 0.014. Education was related to the attitude of female adolescent (p-vaue = 0.000) and attitudes of male adolescent (p-value = 0.016). Economic status was related to the attitude of female adolescent (p-value = 0.000) and attitudes of male adolescents (p-value = 0.035). Characteristics had a relationship with adolescent attitudes in conducting pre-primary sex behavior. Therefore, it is necessary to have appropriate efforts to prevent adolescent risk behavior in accordance with the characteristics and needs of today’s youth